Antibacterial Activity of Sea Cucumber (Stichopus ocellatus) Against Bacillus cereus and Escherichia coli Bacteria. Issue 1 (November 2021) - Sukmiwati, M; Ilza, M; Diharmi, A; Sherrin, S
Abstract: Sea cucumber (Stichopus ocellatus) is one of the bioresources that has not been utilized optimally. Samples were collected in the coastal sea of Lengkang Island, Batam. This study was aimed to determine the bioactive compound and antibacterial activity of sea cucumber extract against Bacillus cereus and Escherichia coli . The research method used was an experiment with a series of experiments, namely the extraction of sea cucumbers with ethanol as a solvent. Parameter analysis were identification of bioactive compound (phytochemical) and antibacterial activity against Bacillus cereus and Escherichia coli using well diffusion method. The treatment for the antibacterial activity test used various extract concentrations consisting of 125, 250, 375, and 500 g/mL with three replications. The results of the identification of the bioactive compounds of sea cucumber extract showed that the ethanolic extract of sea cucumbers contained saponins, alkaloids, and phenolics. The analysis of the antibacterial activity of the sea cucumber extract showed that the diameter of the inhibition zone of the ethanol extract at a solvent ratio of 1: 5 (w/v) and at a concentration of 500µ/mL against B. cereus was 14.66 ± 0.37mm and E. coli was 15.45. ±0.17mm. The results showed that the highest antibacterial activity of sea cucumber extract against E. coli bacteria.